2018
DOI: 10.1002/eji.201847677
|View full text |Cite
|
Sign up to set email alerts
|

Eomes controls the development of Th17‐derived (non‐classic) Th1 cells during chronic inflammation

Abstract: It is well accepted that Th17 cells are a highly plastic cell subset that can be easily directed toward the Th1 phenotype in vitro and also in vivo during inflammation. However, there is an ongoing debate regarding the reverse plasticity (conversion from Th1 to Th17). We show here that ectopic ROR-γt expression can restore or initiate IL-17 expression by non-classic or classic Th1 cells, respectively, while common pro-Th17 cytokine cocktails are ineffective. This stability of the Th1 phenotype is at least part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
74
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 50 publications
4
74
0
Order By: Relevance
“…Th1 cells are traditionally considered a highly stable cell subset. Indeed, we and others have shown that Th1 cells (either classic or non‐classic) are resistant to the activity of pro‐Th17 cytokines . Only ROR‐ γ t forced expression by way of lentiviral vector can trigger IL‐17 production by Th1 cells .…”
Section: Plasticity Of Th17 Cellsmentioning
confidence: 91%
See 4 more Smart Citations
“…Th1 cells are traditionally considered a highly stable cell subset. Indeed, we and others have shown that Th1 cells (either classic or non‐classic) are resistant to the activity of pro‐Th17 cytokines . Only ROR‐ γ t forced expression by way of lentiviral vector can trigger IL‐17 production by Th1 cells .…”
Section: Plasticity Of Th17 Cellsmentioning
confidence: 91%
“…In parallel, non‐classic Th1 cells acquire Th1 features such as expression of the chemokine receptor CXCR3 and of the transcription factor Tbet . Non‐classic Th1 cells produce IFN‐ γ and granulocyte–macrophage colony‐stimulating factor (GM‐CSF) as classic Th1 cells do . More recently we showed that also tumor necrosis factor‐ α (TNF‐ α ) can promote the development of non‐classic Th1 cells from Th17 cells .…”
Section: Plasticity Of Th17 Cellsmentioning
confidence: 99%
See 3 more Smart Citations